2001
DOI: 10.2337/diacare.24.3.500
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic Mitochondrial Genotype in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -To evaluate the significance of a longevity-associated mitochondrial genotype (Mt5178A) derived from a C 3 A transversion at nucleotide position 5178 of mitochondrial DNA, which causes a Leu-to-Met substitution within the NADH dehydrogenase subunit 2 gene, in type 2 diabetic subjects.RESEARCH DESIGN AND METHODS -Mt5178 typing was done by polymerase chain reaction-restriction fragment-length polymorphism with the restriction enzyme AluI in 1,148 type 2 diabetic Japanese subjects, and the results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 23 publications
0
32
4
Order By: Relevance
“…Associations between other candidate polymorphisms and carotid IMT in patients with type 2 diabetes were also recently reported. Leucine 7 to proline 7 polymorphism in the neuropeptide Y gene was associated with advanced carotid atherosclerosis (30), and mitochondrial genotype Mt5178A was shown to be associated with lower carotid IMT values compared with the MT5178C allele (31). We showed in this study that the C807T polymorphism of ␣2 integrin is another candidate polymorphism involved in carotid IMT and carotid plaque.…”
Section: ) Nsmentioning
confidence: 61%
“…Associations between other candidate polymorphisms and carotid IMT in patients with type 2 diabetes were also recently reported. Leucine 7 to proline 7 polymorphism in the neuropeptide Y gene was associated with advanced carotid atherosclerosis (30), and mitochondrial genotype Mt5178A was shown to be associated with lower carotid IMT values compared with the MT5178C allele (31). We showed in this study that the C807T polymorphism of ␣2 integrin is another candidate polymorphism involved in carotid IMT and carotid plaque.…”
Section: ) Nsmentioning
confidence: 61%
“…7 In type-II diabetic Japanese, the intima-media thickness in the bilateral carotid arteries is significantly larger in the mt5178C group than in the mt5178A group. 8 Moreover, Wang et al 11 reported that the mean age at onset of diabetes was significantly lower in Japanese patients carrying mt5178C than in those carrying mt5178A. In addition to these metabolic differences, mt5178 A/C polymorphism may partially influence life expectancy by influencing the blood-pressureelevating effects of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…6 In fact, mt5178A was reported to exert antiatherogenic effects. [7][8][9] We reported that serum high-density lipoprotein cholesterol levels were significantly higher in men carrying mt5178A than in men carrying mt5178C, and that triglyceride levels were significantly lower in women carrying mt5178A than in women carrying mt5178C. 7 Blood pressure and serum lipid levels are crucial factors in the pathology of age-related circulatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide polymorphism (C5173A), resulting in a leucine to methionine amino acid substitution in the mitochondrially encoded NADH dehydrogenase subunit 2 (mt-ND2) gene, has been associated with resistance against T1D in an autoantibody-positive Japanese population (32). In addition to T1D, this allele (mt-Nd2 a ) has been reported to provide resistance against other ROS-mediated pathologies: atherosclerosis (33), myocardial infarction (34,35), and high blood pressure (36)), and correlates with increased longevity (37) and reduced serum lipid levels (38). We hypothesize that decreased mitochondrial ROS production mediated by mt-Nd2 a plays a key role in this allele's protective effects.…”
mentioning
confidence: 99%